Giant cell angiofibroma of gingiva in tuberous sclerosis complex: a case report and literature review - Qiaochu Sun; Jaeyoung Ryu; Young Kim (BMC, 2024)
Abstract Background Tuberous sclerosis complex (TSC) is a rare, complex genetic disorder characterized by hamartomas and neoplastic lesions in various organ systems. With the development of radiology and gene testing, the diagnostic criteria for TSC were updated in 2012 at the International Consensus Conference. Intraoral fibromas have long been associated with TSC. However, the incidence of giant cell angiofibroma (GCA) in TSC patients is extremely rare. Here, we report the first case of GCA in the gingival tissue of a patient with TSC. Case presentation A 41-year-old woman first visited the Department of Oral and Maxillofacial Surgery, Chonnam National University Dental Hospital, complaining of gingival enlargement. Clinical examination revealed several manifestations associated with TSC, including intraoral fibromas, facial angiofibromas, dental enamel pits, ungual fibromas, "confetti" skin lesions, hypomelanotic macules, and a shagreen patch. Intraoral examination revealed a 6.0 × 5.0 cm gingival overgrowth on the left mandible. Surgical excision was performed, and subsequent histopathological examination confirmed the diagnosis of GCA. There was no evidence of recurrence within the 24- months of surgery. Conclusions We report the first case of GCA in the gingival tissue of a patient with TSC. This report would contribute to an improved understanding of this rare disease. However, further case reports are necessary to clarify the relationship between GCA and TSC.